Gender and water in Morocco: mainstreaming gender dimensions in integrated water resources management in Morocco - Maaroufi T. (Mainstreaming gender dimensions in water management for food security and food safety, 2007)
This paper outlines AMSED (Association Marocaine de Solidarité et de Développement) evolution in implementing its Morocco action plan. The paper starts with an overview of Morocco : its geography, its socio-cultural composition, the evolution of population, its economy and the general political infrastructure. Then an overview of the state of human development of the country is given with some data on human development indicators. The second part presents the natural resources of the country focusing on water and its different uses, especially in agriculture (irrigation). It briefly presents the state of water in Morocco, women's access to water resources and their role in agriculture and irrigation. This part ends with the presentation of AMSED experience in the field of water resources preservation and development. The third and last part of the paper gives the state of the art of AMSED actions within the GEWAMED project: the major activities carried out, as compared with those scheduled in the action plan 2006 and the actions proposed for the year 2007.
2. Regional Coordination Workshop of GEWAMED (Mainstreaming Gender Dimensions into Water Resources Development and Management in the Mediterranean Region), 2007/03/12-14, Larnaca (Cyprus)